2021
DOI: 10.1101/2021.03.08.21253065
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of previous COVID-19 on immune response after a single dose of BNT162b2 SARS-CoV-2 vaccine

Abstract: Immune response after a single-dose of BNT162b2 vaccine is markedly increased in health care workers with previous SARS-CoV2 exposure, as assessed by positive SARS-CoV2 IgG, particularly after moderate-severe COVID-19. These data may inform the priority of the boosting mRNA second dose in times of vaccine shortage.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The geometric mean of spike IgG after the second injection was 17378 AU/mL, which was higher than corresponding values measured in a naïve Spanish COVID-19 population, 12 but similar to another study. 13 In addition, the range of values was quite broad, from 2826 AU/mL to 70272 AU/mL.…”
Section: Discussionsupporting
confidence: 84%
“…The geometric mean of spike IgG after the second injection was 17378 AU/mL, which was higher than corresponding values measured in a naïve Spanish COVID-19 population, 12 but similar to another study. 13 In addition, the range of values was quite broad, from 2826 AU/mL to 70272 AU/mL.…”
Section: Discussionsupporting
confidence: 84%
“…By Poisson model regression analysis, the reduced incidence among HCW adjusting for the background changes in the general population remained statistically and clinically significant: 3% reduction (IRR 0.272; 95% CI 0.164-0.451 p<0.001) after the first dose of the vaccine and 92 % (IRR 0.176, 95% CI 0.033-0.174; p<0.001) after the second dose (Supplemental Tables and Figure). It is conceivable that the response to the vaccine among HCW may have been boosted by a previous exposure to the virus [12,13]. .…”
Section: Resultsmentioning
confidence: 99%
“…Our results after a single dose of the vaccine might not be extrapolated to other settings: our vaccination program was extended to all HCW, including HCW with previous SARS-COV-2 documented infection [7]. We and others have recently shown that HCW with a previous SARS-CoV-2 infection exhibit a strong serologic response to the first dose of the vaccine, reaching higher IgG anti spike titre than that obtained after full vaccination in SARS-CoV-2 naïve individuals [12,13]. Other vaccination programs (excluding previously infected HCW) may exhibit a lower protection [2].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the values cannot be comparatively evaluated because data obtained using Abbot-Quant® methodology, although expressed as BAU/mL, are in general lower than those reported by Roche-Elecsys® [18] . Lastly, even though published information on immunogenicity after full-dose vaccine administration is still limited and occasional, some experimental results from the literature as regards to the immune response after the second dose of BNT162b2 vaccine in a homologous schedule were evaluated [18] , [23] , [24] , [25] , [26] , [27] , [28] . The required conditions for the comparative study of VORs data were identical methodology (Abbott-Quant®) and exact time point for blood sampling (±1 day).…”
Section: Discussionmentioning
confidence: 99%